Estratégias de hedge: Testando a eficiência da variância mínima com contratos futuros de Ibovespa - Gavioli, Luís Eduardo de Campos (Universidade Federal de São Carlos, 2025)
The primary objective of this study is to evaluate the efficiency of hedging with Ibovespa futures contracts using the minimum variance method, considering periods of high and low returns for this index, as well as periods of stability. These criteria allow for the assessment of three distinct economic situations and provide relevant information for decision-making across different scenarios. Given that the Ibovespa Index cannot be directly acquired, this method is also tested for the ETF BOVA11, a fund that replicates the Ibovespa and allows investments by market participants in the stock exchange environment. The tests were conducted for the Ibovespa Index and the ETF BOVA11 across three distinct market periods between 2020 and 2024. To perform the hedge, the Ibovespa futures contracts INDJ20, INDQ20, and INDJ24 were used. The research concluded that determining the optimal hedge ratio using the minimum variance method generally leads to a reduction in price fluctuations for the portfolios under consideration. This effect is subtler when compared to the hedge with a 1:1 ratio but remains highly significant relative to unhedged portfolios.
Hedging Strategies: Testing the Efficiency of Minimum Variance with Ibovespa Futures Contracts
Keywords: Hegde; Ibovespa; Ações; Contratos Futuros; Stocks; Futures Contracts; CIENCIAS SOCIAIS APLICADAS::ECONOMIA